Antibiotic-Prescribing Practices for Management of Childhood Diarrhea in 3 Sub-Saharan African Countries: Findings From the Vaccine Impact on Diarrhea in Africa (VIDA) Study, 2015–2018. (19th April 2023) - Awuor, Alex O; Ogwel, Billy; Powell, Helen; Verani, Jennifer R; Sow, Samba O; Hossain, M Jahangir; Ochieng, John B; Juma, Jane; Jamka, Leslie P; Roose, Anna; Doh, Sanogo; Deichsel, Emily L; et al.
Abstract: Background: Despite antibiotic prescription being recommended for dysentery and suspected cholera only, diarrhea still triggers unwarranted antibiotic prescription. We evaluated antibiotic-prescribing practices and their predictors among children aged 2–59 months in the Vaccine Impact on Diarrhea in Africa (VIDA) Study performed in The Gambia, Mali, and Kenya. Methods: VIDA was a prospective case-control study (May 2015–July 2018) among children presenting for care with moderate-to-severe diarrhea (MSD). We defined inappropriate antibiotic use as prescription or use of antibiotics when not indicated by World Health Organization (WHO) guidelines. We used logistic regression to assess factors associated with antibiotic prescription for MSD cases who had no indication for an antibiotic, at each site. Results: VIDA enrolled 4840 cases. Among 1757 (36.3%) who had no apparent indication for antibiotic treatment, 1358 (77.3%) were prescribed antibiotics. In The Gambia, children who presented with a cough (adjusted odds ratio [aOR]: 2.05; 95% confidence interval [95% CI]: 1.21–3.48) were more likely to be prescribed an antibiotic. In Mali, those who presented with dry mouth (aOR: 3.16; 95% CI: 1.02–9.73) were more likely to be prescribed antibiotics. In Kenya, those who presented with a cough (aOR: 2.18; 95% CI: 1.01–4.70), decreased skin turgor (aOR: 2.06; 95% CI: 1.02–4.16), and were very thirsty (aOR: 4.15; 95% CI: 1.78–9.68) were more likely to be prescribed antibiotics. Conclusions: Antibiotic prescription was associated with signs and symptoms inconsistent with WHO guidelines, suggesting the need for antibiotic stewardship and clinician awareness of diarrhea case-management recommendations in these settings. Abstract : Inappropriate antibiotic prescribing for diarrheal diseases can promote antimicrobial resistance. In VIDA, unnecessary or incorrect antibiotics were prescribed for 77% of diarrhea and 41% of dysentery cases. Interventions are needed to promote judicious adherence to international guidelines in low-/middle-income countries.